INTERFAITH MARRIAGE IN ISLAMIC FAMILY LAW: THE PERSPECTIVE OF CLASSICAL FIQH AND THE COMPILATION OF ISLAMIC LAW - Sri Nurmalinda; Heri Firmansyah (PT. Jurnal Center Indonesia Publisher, 2026)
Interfaith marriage is a classic yet ever-relevant issue in Islamic family law. This study aims to examine the legal status of interfaith marriage in Islamic family law through classical and contemporary fiqh perspectives, as well as its arrangement in the Compilation of Islamic Law (KHI) in Indonesia. The method used is normative legal research with statutory and conceptual approaches, referring to authoritative classical tafsir and fiqh works such as Jami' al-Bayan by al-Tabari, al-Jami' li Ahkam al-Qur'an by al-Qurtubi, Tafsir Ibn Kathir, al-Umm by Imam al-Shafi'i, and al-Mughni by Ibn Qudamah, as well as contemporary works such as Fiqh al-Sunnah by Sayyid Sabiq and the works of Wahbah al-Zuhaili and Yusuf al-Qaradawi. The findings indicate that classical jurists unanimously prohibit the marriage of a Muslim woman to a non-Muslim man and the marriage of a Muslim man to a polytheist (mushrik) woman, but differ regarding the marriage of a Muslim man to a woman of the People of the Book (Ahl al-Kitab). Meanwhile, the KHI takes a stricter stance by prohibiting all forms of interfaith marriage, in line with the principle of preventing harm (sadd al-dhari'ah) and the MUI Fatwa of 2005. This study concludes that the KHI represents a contextualization of fiqh adapted to the conditions of Indonesian society.